Advances and Perspectives in Cancer Nanotherapy: The Added- Value of Nanocarriers - Demetzos, Costas; Pippa, Natassa; Pispas, Stergios (Current Nanomedicine, 2017)
Background: Cancer nanotherapy integrate efficacious molecules that otherwise could not be used because of their high toxicity and exploit multiple mechanisms of actions (e.g. multifunctional gels, functional polymers, hybrid nanoparticles). The aim of this review is to contemplate the designed and developed nanoparticulate systems that exhibit a benefit in cancer nanotherapy strongly related with the properties of the nanoplatforms formulation. Method: Systemic search and review of papers regarding cancer nanotherapy took place via MedLine and abstract presentations of international conferences. Results: The recent advances in the development of self-assembled structures of lipids- (i.e. liposomes, niosomes, etc.) and of polymers- (micelles, polymersomes, dendrimers, polymeric nanoparticles, hydrogels, etc.) as well as clinical perspectives will be discussed on the basis of pharmaceutical nanotechnology considerations, and on their in vitro and in vivo evaluation. Chimeric/Mixed nanoplatforms that are composed at least of two different in nature biomaterials (i.e. phospholipids and polymers) can be considered as new technological outcomes in cancer nanotherapy that could be able to deliver anticancer drugs to specific tissues. Conclusion: They can improve the pharmacokinetics/pharmacodynamics behavior of antitumor molecules, affect their total bioavailability and provide innovative delivery behavior due to their nanotechnological profile.
Keywords: micelles